Effectiveness of health care worker training on the oral health of elderly residents of nursing homes - Nicol R, Sweeney MP, McHugh S, Bagg J. (Blackwell Synergy, 2005)
The aim of this study was to evaluate the effect of a staff training programme on mouth care on the oral health of elderly residents of long-term care institutions.